2011
DOI: 10.1152/ajpheart.01056.2010
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy limits acute myocardial infarction induced by permanent coronary artery occlusion

Abstract: Ischemia is known to potently stimulate autophagy in the heart, which may contribute to cardiomyocyte survival. In vitro, transfection with small interfering RNAs targeting Atg5 or Lamp-2 (an autophagy-related gene necessary, respectively, for the initiation and digestion step of autophagy), which specifically inhibited autophagy, diminished survival among cultured cardiomyocytes subjected to anoxia and significantly reduced their ATP content, confirming an autophagy-mediated protective effect against anoxia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
127
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(138 citation statements)
references
References 42 publications
9
127
0
1
Order By: Relevance
“…Having said this, it remains controversial whether activation of autophagy is beneficial or detrimental in load-induced remodeling (7,32), whereas augmenting autophagy has been more consistent in protecting against postischemic remodeling (33)(34)(35). Nakai et al demonstrated that the cardiac-specific knock-out of ATG5 in adult mice led to cardiac hypertrophy, LV dilatation, and contractile dysfunction (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Having said this, it remains controversial whether activation of autophagy is beneficial or detrimental in load-induced remodeling (7,32), whereas augmenting autophagy has been more consistent in protecting against postischemic remodeling (33)(34)(35). Nakai et al demonstrated that the cardiac-specific knock-out of ATG5 in adult mice led to cardiac hypertrophy, LV dilatation, and contractile dysfunction (7).…”
Section: Discussionmentioning
confidence: 99%
“…These conflicting reports regarding the protective versus maladaptive effects of specific autophagy regulators stand in contrast to data from mouse and rat LAD occlusion model of MI. In this model, Kanamori et al found in mouse that levels of autophagy were greatest in the infarct border zone during the first week post-MI, then greatest in remote areas of the heart during the chronic stage (3 weeks post-MI) and that blocking autophagy (with Baf-A1) exacerbated cardiac dysfunction, although enhancing autophagy (with rapamycin) reduced cardiac dysfunction and remodeling (33,34). Consistent with this, Buss et al reported in rat that the mTOR inhibitor everolimus also increased autophagy and prevented adverse cardiac remodeling post-MI (35).…”
Section: Discussionmentioning
confidence: 99%
“…During these processes, CMs are able to elicit the cardioprotective process of autophagy to alter the fate of struggling CMs in order to survive the hypoxic cellular conditions and prevent cell death. The interaction between each of these cellular processes with common signaling mediators (Figure 2) will determine the fate of ischemic CMs with the balance that occurs in the peri-infarct area most likely playing a vital role in CM preservation of functional capacity via appropriate autophagic flux and mitigation of apoptosis and inflammation [27,65,92]. With an in-depth understanding of the factors that determine the balance between cellular survival and death of CMs in response to acute MI, novel therapeutics can be developed to promote CM survival during the initial ischemic insult and improve cardiac function following MI.…”
Section: Resultsmentioning
confidence: 99%
“…In a permanent coronary artery occlusion model, autophagy was shown to be activated within 30 minutes of ischemia and noted to be strongly activated in the peri-infarct area [65]. Inhibition of mTOR with everolimus resulted in increased LC3 expression in the border zone of infarction, also suggesting autophagic activity is more prominent in the peri-infarct CMs (Figure 2) [66].…”
Section: Autophagymentioning
confidence: 99%
“…This is an evolutionally conserved process crucial for normal tissue homeostasis. Accumulating evidence suggests that autophagy is stimulated by ischemia and actually contributes to cardiomyocyte survival [26,27]. A recent study has shown that autophagy induced by ischemic preconditioning is essential for cardioprotection [28].…”
Section: Discussionmentioning
confidence: 99%